2013
DOI: 10.1101/lm.028894.112
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal and postrhinal, but not lateral entorhinal, cortices are essential for acquisition of trace eyeblink conditioning

Abstract: The acquisition of temporal associative tasks such as trace eyeblink conditioning is hippocampus-dependent, while consolidated performance is not. The parahippocampal region mediates much of the input and output of the hippocampus, and perirhinal (PER) and entorhinal (EC) cortices support persistent spiking, a possible mediator of temporal bridging between stimuli. Here we show that lesions of the perirhinal or postrhinal cortex severely impair the acquisition of trace eyeblink conditioning, while lateral EC l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Importantly, the same study reported that the entorhinal damage does not impair acquisition when the interval is shortened to 300 ms. Similarly, damage mainly to the lateral portions of the entorhinal cortex (LE) does not have any effect on acquisition in the paradigm with the 250 ms interval (Suter et al, ). Taken together, these results suggest that that the DLE is necessary for memory acquisition only when the interstimulus interval is sufficiently long.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the same study reported that the entorhinal damage does not impair acquisition when the interval is shortened to 300 ms. Similarly, damage mainly to the lateral portions of the entorhinal cortex (LE) does not have any effect on acquisition in the paradigm with the 250 ms interval (Suter et al, ). Taken together, these results suggest that that the DLE is necessary for memory acquisition only when the interstimulus interval is sufficiently long.…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, half of the rabbits received explicitly unpaired presentations of the CS and US to assess nonassociative contributors to responding [9, 13, 33–36]. Importantly, the interval between the CS and US for paired rabbits was more than 500 ms creating a significant trace which previous studies by a number of groups have shown made classical conditioning dependent on the hippocampus [1820, 3740] and prefrontal cortex [23, 25, 27, 29, 4145] in addition to the cerebellum. In each of our trace conditioning experiments, acquisition of a conditioned response was a function of the trace interval and usually took many days of training to reach asymptote, and this asymptote tended to be lower than that seen using delay conditioning [17].…”
Section: The Effects Of Cholesterol On Learningmentioning
confidence: 99%
“…In trace eyeblink conditioning (TEBC), the EC is necessary for memory acquisition [4,5] as well as the expression of one-day-old (recent) and one-month-old (remote) memory [6]. The role of the EC in memory acquisition and initial expression is expected given its role as a primary input structure to the hippocampus, which is necessary for memory acquisition and initial retention [7-11].…”
Section: Introductionmentioning
confidence: 99%